The role of folic acid in fetal programming of birth phenotypes and early human development: a biopsychosocial perspective. (5th July 2013) - Salihu, H. M.; Salinas-Miranda, A.; de la Cruz, C.; Alio, A. P.
Abstract : Preterm birth, low birthweight, intrauterine growth retardation and small for gestational age are birth phenotypes that significantly contribute to life-long morbidity and mortality. This review examines the epidemiologic and biologic evidence of folic acid (FA) as a potential population-based intervention to curtail some adverse birth phenotypic expressions, and by extension, their later physical and neurodevelopmental consequences. We outlined a feto-placental adaptation categorization taking into account how prenatal insults may be encoded in fetal development, the adaptive success of the feto-placental response, and subsequent expression in the health of the fetus. Although there are plausible biological pathways that can be implicated, we found that the epidemiological evidence on the role of perinatal FA nutriture and fetal programming of adverse birth phenotypes is still inconclusive. Because biologic and epidemiological considerations alone do not suffice in deciphering the utility of FA in averting adverse birth phenotypes, we proposed a biopsychosocial model that takes into account multi-layered psychosocial contexts for improving subsequent research studies in this area.